The essential meaning of the Way and Virtue: Yan Zun and “Laozi learning” in early Han China - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2016)
In a short essay written in 1924, Yang Shuda 楊樹達 called attention to the sig-nificant growth of “Laozi learning" (Laoxue 老學) during the Han period (206B.C. - A.D. 220).1 On the basis of biographical and bibliographical references inthe early dynastic histories especially, Yang identified some fi 仿 Han figures ashaving contributed to this development. The Laozi itself, according to one tradi-tion, was accorded the status of a “classic" (Jing經) during the reign of emperorJing 景(1 56-141 B.C.).2 While this claim is still open to debate , there is littledisagreement 血 at the title Daojng gained currency by the end of the FormerHan dynasty (A.D. 8).3 Since that time ，的 is well known, hundreds of commentaries have appeared, all seeking to bring ou叫t the “full" meaning of theof the Way and Virtue."